How Sales Interpersonal Skills Drive Wedding Organizers to Recommend Venues B2B - Clearesta Adinda; Ni Kadek Swandewi; Prastha Adyatma; Darelia Damara Wikan (Penerbit Goodwood, 2025)
Purpose: This study examines the influence of sales interpersonal skills on wedding organizers' (WOs) trust and their willingness to recommend venues in business-to-business (B2B) relationships. Methodology/approach: A sample of 41 members of the Bali Wedding Association was used, with 15 indicators assessed on a 5-point Likert scale to evaluate the impact of interpersonal skills on trust and recommendation behaviours. It is that these members do not all belong to the same organization. Results/findings: The results show that sales interpersonal skills significantly enhance both the trust that WOs place in sales personnel and their willingness to recommend venues. Additionally, the study reveals that trust acts as a mediator in this relationship, meaning that interpersonal skills not only directly impact recommendations but also do so indirectly by fostering trust. Conclusion: Despite the small sample size and geographic focus, which limit the generalizability of the findings, this research provides valuable insights into the key drivers of successful B2B relationships in the wedding industry. Limitation: The study suggests that sales professionals and venue managers should prioritize developing strong interpersonal skills to enhance trust and foster positive recommendations from WOs. Future research should explore larger and more diverse samples to verify these findings across different regions and industries, expanding the understanding of interpersonal dynamics in B2B relationships. Contribution: Specifically, it highlights the crucial role of interpersonal skills in building trust, which in turn increases the likelihood of venue recommendations.